Use of Intravesical Injections of Platelet-Rich Plasma for the Treatment of Bladder Pain Syndrome: A Comprehensive Literature Review - Francesco Trama; Ester Illiano; Alessandro Marchesi; Stefano Brancorsini; Felice Crocetto; Savio Domenico Pandolfo; Alessandro Zucchi; Elisabetta Costantini (MDPI AG, 2021)
Background: Bladder pain syndrome/interstitial cystitis (BPS/IC) or primary bladder pain syndrome (PBPS) is a complex and poorly understood condition. This comprehensive review aimed to discuss the potential application of platelet-rich plasma (PRP) in the treatment of BPS/IC. The pathophysiology of BPS/IC is characterized by urothelial damage that triggers a chain of events leading to chronic inflammation and other conditions. Frequently, in subjects affected by BPS/IC, recurrent urinary tract infection (rUTI) is associated with difficult therapeutic management. For these reasons, many oral and intravesical treatments (e.g., antibiotic therapy and intravesical anesthetic instillations) have been proposed to alleviate the symptoms of IC/BPS. However, the limitation of these treatments is the short duration of improvement. The purpose of this review is to analyze the efficacy of intravesical PRP injections in subjects with PBS/IC and to try to understand the potential therapeutic effects on the pathophysiology of this disease. Methods: A nonsystematic literature search using Pubmed, EMBASE, Scopus, Web of Science, Medline was performed from January 2000 to August 2021. The following terms were combined to capture relevant publications: "platelet-rich plasma", "interstitial cystitis", "PRP", "bladder pain syndrome", and "painful bladder syndrome". Results: After exclusion of non-pertinent studies/articles, we have analyzed 5 studies. In detail, 2 articles concerned preclinical studies in which animal models were used. The authors showed an improvement in the histological pattern with less bleeding in treated subjects, a lower presence of inflammatory cytokines and an increase in the mitotic index of urothelial cells in animals treated with intravesical PRP. In the three prospective clinical trials analyzed, patients with BPS/IC who underwent monthly intravesical PRP injections were found to have a statistically significant improvement in symptoms with modulation of growth factors and inflammatory proteins. Conclusions: New evidence suggests that treatment with intravesical PRP could improve urothelial regeneration and reduces chronic inflammation in BPS/IC, modifying the clinical history of its pathology.